Factors Influencing Academic Achievement in EFL Pupils: A Comparative Study Between Government-Funded and Tuition-Based Primary Schools in Souk Ahras - Widad GOUASMIA (My University, 2025)
ABSTRACT Education plays an important role in developingchildren’s intellect, preparing them for real-life tasks, and helping themcreate a prosperous future.One of the necessary elements is the mastery of foreign languages, especially English which has achieved global recognition as essential for academic and professional progression. In this regard, incorporating English into the Algerian primary school curriculum represents a vital step toward enhancing language proficiency from an early age.This research scrutinizes the factors influencing academic achievement among English as a Foreign Language (EFL) pupils in Souk Ahras, focusing on a comparative analysis between government-funded and tuition-based schools. The research involved 68 pupils across the three schools, in addition to their parents, and the three teachers of English. The data was collected through interviews with teachers, questionnaires administered to parents, and direct classroom observations.Specifically, the research explores the perceived influenceof teaching methods, classroom environment, parental involvement, and the availability of educational resources on pupil’sacademic achievement in English. Through both theoretical insights and field data, the research highlights the advantages and challenges each educational setting presents. The findings reveal that while tuition-based schools generally benefit from more favorable learning conditions and resource availability, government-funded schools often struggle with outdated materials and infrastructural constraints. Nonetheless, the presence of dedicated teachers and active parental engagement remains a strong predictor of pupil success across both schools. The research concludes by emphasizing the need for balanced investment in human and material resources to enhance EFL outcomes and ensure equitable learning opportunities for all pupils. --------------- الملخص يلعب التعليم دورًا جوهريًا في تطوير قدرات الأطفال الفكرية، وتمكينهم من مواجهة تحديات الحياة الواقعية، وبناء مستقبل واعد. ومن بين الركائز الأساسية لهذا التعليم، يبرز إتقان اللغات الأجنبية، وعلى رأسها اللغة الإنجليزية التي تحظى بمكانة عالمية كأداة محورية للتطور الأكاديمي والمهني. وفي هذا الإطار، يُعد إدراج اللغة الإنجليزية ضمن مناهج التعليم الابتدائي في الجزائر خطوة استراتيجية لتعزيز الكفاءة اللغوية لدى التلاميذ منذ سن مبكرة.يركز هذا البحث على دراسة العوامل المؤثرة في التحصيل الأكاديمي لدى تلاميذ اللغة الإنجليزية كلغة أجنبية بولاية سوق أهراس، من خلال مقارنة منهجية بين المدارس العمومية والمدارس الخاصة المعترف بها والممولة عبر الرسوم الدراسية. شملت العينة 68 تلميذًا موزعين على ثلاث مدارس، إضافة إلى أولياء أمورهم ومعلمي اللغة الإنجليزية الثلاثة. وتم جمع البيانات باستخدام أدوات متنوعة، شملت المقابلات الشفهية مع المعلمين، والاستبيانات الموجهة لأولياء الأمور، فضلاً عن الملاحظة المباشرة داخل الفصول الدراسية.يتناول البحث بصورة تحليلية أثر كل من أساليب التدريس، وبيئة القسم، ومشاركة الوالدين، وتوفر الموارد التعليمية، على الأداء الأكاديمي للتلاميذ. واستنادًا إلى الأطر النظرية والنتائج الميدانية، يكشف البحث عن المزايا والتحديات التي تميز كل نمط من أنماط التعليم. وقد أظهرت النتائج أن المدارس الخاصة تستفيد عمومًا من بيئة تعليمية أكثر ملاءمة وموارد مادية أفضل، في حين تعاني المدارس العمومية من نقص في تحديث الوسائل التعليمية وضعف في البنية التحتية. ومع ذلك، تبيّن أن وجود معلمين ملتزمين ومشاركة فعالة من قبل أولياء الأمور يظل عنصرًا حاسمًا في تحسين نتائج التحصيل في كلا السياقين.ويخلص البحث إلى ضرورة إحداث توازن في الاستثمارات بين الموارد البشرية والمادية، لضمان تعليم فعال وشامل للغة الإنجليزية كلغة أجنبية، وتوفير فرص تعليمية عادلة ومتساوية لجميع التلاميذ، بغض النظر عن نوع المؤسسة التعليمية. -------------- Résumé L’éducation joue un rôle important dans le développement de l’intellect des enfants, les prépare à des tâches réelles et les aide à créer un avenir prospère. L’un des éléments nécessaires est la maîtrise des langues étrangères, en particulier de l’anglais qui a atteint une reconnaissance mondiale comme essentielle pour la progression académique et professionnelle. À cet égard, l’intégration de l’anglais dans le programme d’enseignement primaire algérien représente une étape essentielle vers l’amélioration des compétences linguistiques dès le plus jeune âge. Cette recherche examine les facteurs qui influencent le rendement scolaire des élèves d’Anglais comme une langue étrangère (EFL) à Souk Ahras, en se concentrant sur une analyse comparative entre les écoles subventionnées par le gouvernement et les écoles fondées sur les frais de scolarité. La recherche a impliqué 68 élèves des trois écoles, en plus de leurs parents et les trois professeurs d’anglais. Les données ont été recueillies au moyen d’entrevues avec des enseignants, de questionnaires administrés aux parents et d’observations directes en classe. Plus précisément, la recherche explore l’influence perçue des méthodes d’enseignement, de l’environnement en classe, de la participation des parents et de la disponibilité des ressources éducatives sur les résultats scolaires des élèves en anglais. Grâce à des connaissances théoriques et des données de terrain, la recherche met en évidence les avantages et les défis que présente chaque environnement éducatif. Les résultats révèlent que si les écoles à frais de scolarité bénéficient généralement de conditions d’apprentissage plus favorables et de ressources disponibles, les écoles financées par le gouvernement ont souvent du mal avec des matériaux désuets et des contraintes infrastructurelles. Néanmoins, la présence d’enseignants dévoués et l’engagement actif des parents demeurent un indicateur important de la réussite des élèves dans les deux écoles. La recherche conclut en soulignant la nécessité d’un investissement équilibré dans les ressources humaines et matérielles pour améliorer les résultats de l’EFL et assurer des possibilités d’apprentissage équitables pour tous les élèves.
Keywords: Academic achievement; classroom environment; educational resources; government-funded school; parental involvement; teaching methods; tuition-based school; :التحصيل الأكاديمي؛ بيئة الفصل؛ الموارد التعليمية؛ المدرسة العمومية؛ المدرسة الخاصة؛ مشاركة الوالدين؛ أساليب التدريس.: Réussite scolaire; milieu de classe; ressources éducatives; école financée par le gouvernement; participation des parents; méthodes d’enseignement; école fondée sur les frais de scolarité